The Feminisation of Belgian Local Party Politics - Devroe, Robin; Erzeel, Silvia; Meier, Petra (Politics of the Low Countries, 2020)
This article investigates the feminisation of local politics. Starting from the observation that the representation of women in local electoral politics lags behind the regional and federal level, and taking into account the relevance of local party branches in the recruitment and selection of candidates for elections, we examine the extent to which there is an ‘internal’ feminisation of local party branches and how this links to the ‘external’ feminisation of local electoral politics. Based on surveys among local party chairs, the article maps patterns of feminisation over time and across parties, investigates problems local branches encounter in the recruitment of candidates for local elections, and analyses the (attitudes towards the) measures taken to further the integration of women in local electoral politics. We conclude that internal and external feminisation do not always go hand in hand and that local politics continues to be a male-dominated political biotope.